The financial and non-financial factors that influence JSE-listed South African retailers' decision to lease or own their corporate real estate, specifically warehouses and distribution centres - Barnard, Shaun Smuts (Department of Construction Economics and Management, 2023)
South African retailers are reliant on Corporate Real Estate not only to grow their footprint, and by implication revenue, but also to enable them to distribute their products to their network of stores. Previous studies have demonstrated that retailers prefer leasing their stores, but no research exists which investigated whether the same principles apply to distribution centres or warehouses which they occupy, specifically in South Africa. This research, provide empirical insight into listed South African retailers' strategy with regards to distribution centres and/or warehouse acquisition methods as well as the financial and non-financial factors which influence their decision and how important these factors are. This study is limited to South African retailers listed on the Johannesburg Stock Exchange. We did not find any noticeable trend exists which provides a framework for South African listed retailers when confronted with the lease-versus-buy decision regarding the acquisition of their Corporate Real Estate assets, specifically distribution centres and/or warehouses. We find that non-financial factors appear to be more important than financial factors when retailers are faced with a lease-versus-buy decision. It is suggested that further research is required to quantify the degree of importance of nonfinancial factors in the lease-versus-buy decision of retailers.